Effect of wearable robot Bot Fit’s hip joint-centered assist torque and voice coach on walking - Shin, Jang-hoon; Byeon, Naeun; Yu, Heeju; Lee, Dokwan; Lee, Hwang-Jae; Lee, Wan-hee (BMC musculoskeletal disorders, 2024)
Background The main key to the 4th industrial era is robots, and wearable robots are incorporated into human healthcare. Samsung Electronics’ Bot Fit is a hip joint-centered assistive robot that can induce walking posture and energetic walking exercises. Methods This study is a cross-section study. Fifty-eight subjects consisting of older and younger adults participated. The straight walking test was conducted under the conditions of bare body, wearing the wearable robot Bot Fit assist mode, and applying voice coach. Spatio-temporal gait parameters were analyzed and the statistical significance level was set at 0.05. Results When assist mode and voice coach were applied, pelvic movement in 3 axes, stride length, and walking speed compared to the bare body increased. In young adults, stride length difference decreased in assist mode 1 and voice coach 1 compared to the bare body. Conclusion Bot Fit’s assist mode and voice coach method positively influence walking efficiency, posture, stride length, and speed, though potential interaction effects between these interventions should be considered. Personalized, real-time adjustments show promise for optimizing walking exercises, warranting further investigation into their long-term and population-specific effects. Trial registration Clinical Research Information Service, KCT0007974. Registered 12/07/2022.